ANALISIS AGEN PELAKSANA IMPLEMENTASI PERATURAN KOMISI PEMILIHAN UMUM NO. 6 TAHUN 2020 PADA PEMILIHAN WALIKOTA DAN WAKIL WALIKOTA DI TENGAH PANDEMI COVID19 PADA PILKADA KOTA MEDAN TAHUN 2020 - Ok Nadhil Auzan; Ari Subowo; Teuku Afrizal (Journal of Public Policy and Management Review, 2022)
The implementation of the Regional Head General Election amid the COVID-19 Pandemic has become a challenge for regional election organizers, namely the General Election Commission, one of which is in the City of Medan. Starting from the change in the timing of the Pilkada, to the obligation to ensure a smooth democratic party by implementing health protocols, presents several challenges, especially in the implementation of the Medan City Election. In this study, the author will conduct a descriptive qualitative research type to conduct in-depth research related to the implementation of regional head elections in Medan City. The results of this study found that the implementation of PKPU policy no. 6 of 2020 at the Medan City KPU has been good with few findings, namely in the aspect of resources, the implementation of PKPU No. 6 of 2020 had experienced problems due to an increase in the budget forfulfilmentlment of health protocols that had not been previly planned. In addition, the KPU an actor is the main actor who has a significant role in the implementation of the Pilkada in Medan City. In terms of adjustments made in the 2020 Medan City election, it is related to the limitation of the number of people and the imposition of sanctions for candidate pairs if they present a crowd at each stage of the Pilkada.